Does green marketing works with consumers? - Kumar M., Dileep (Wulfenia Journal, 2013)
Green and going green is a confused concept in the business sector since, many are going by alternative names such as sustainable marketing, environmental marketing, Eco marketing, organic marketing, etc. Green marketing, also otherwise identified as environmental marketing and sustainable marketing, refers to an organization's efforts at scheming, stimulating, valuing and allocating products that will not damage the environment. Green marketing is essentially a way to brand marketing message in order to capture more of the market by appealing to people's desire to choose products and services that are better for the environment. It is hypothesized in this research that through green marketing it is possible for a company to enhance their brand value on their product to the customers, but may have less chance to influence on consumer purchasing behavior.This study was conducted among 389 customers in Kuala-Lumpur and Penang area Malaysia.The study applied statistical tools like correlation and regression to arrive at the findings. The findings indicate that the companies green marketing campaigns well correlated with brand perception of and buying behavior of consumers. The study provides insight into the dynamic nature of consumer buying behavior.